Impact of the coronavirus disease 2019 (COVID‐19) pandemic on pediatric oncology care in the Middle East, North Africa, and West Asia region: A report from the Pediatric Oncology East and Mediterranean (POEM) group. Issue 18 (10th July 2020) - Saab, Raya; Obeid, Anas; Gachi, Fatiha; Boudiaf, Houda; Sargsyan, Lilit; Al‐Saad, Khulood; Javakhadze, Tamar; Mehrvar, Azim; Abbas, Sawsan Sati; Abed Al‐Agele, Yasir Saadoon; Al‐Haddad, Salma; Al Ani, Mouroge Hashim; et al.
Abstract : Background: Childhood cancer is a highly curable disease when timely diagnosis and appropriate therapy are provided. A negative impact of the coronavirus disease 2019 (COVID‐19) pandemic on access to care for children with cancer is likely but has not been evaluated. METHODS: A 34‐item survey focusing on barriers to pediatric oncology management during the COVID‐19 pandemic was distributed to heads of pediatric oncology units within the Pediatric Oncology East and Mediterranean (POEM) collaborative group, from the Middle East, North Africa, and West Asia. Responses were collected on April 11 through 22, 2020. Corresponding rates of proven COVID‐19 cases and deaths were retrieved from the World Health Organization database. Results: In total, 34 centers from 19 countries participated. Almost all centers applied guidelines to optimize resource utilization and safety, including delaying off‐treatment visits, rotating and reducing staff, and implementing social distancing, hand hygiene measures, and personal protective equipment use. Essential treatments, including chemotherapy, surgery, and radiation therapy, were delayed in 29% to 44% of centers, and 24% of centers restricted acceptance of new patients. Clinical care delivery was reported as negatively affected in 28% of centers. Greater than 70% of centers reported shortages in blood products, and 47% to 62% reported interruptions in surgery and radiation as well as medication shortages. However, bed availability was affected in <30% of centers, reflecting the low rates of COVID‐19 hospitalizations in the corresponding countries at the time of the survey. Conclusions: Mechanisms to approach childhood cancer treatment delivery during crises need to be re‐evaluated, because treatment interruptions and delays are expected to affect patient outcomes in this otherwise largely curable disease. Abstract : The response to the coronavirus disease 2019 (COVID‐19) pandemic has led to significant alterations in access to care for children with cancer. Interventions are needed to mitigate the effects on life‐threatening diseases requiring immediate and uninterrupted therapy, such as childhood cancer.